2020
DOI: 10.1038/s41433-020-0954-5
|View full text |Cite
|
Sign up to set email alerts
|

Seven-year trends in cataract surgery indications and quality of outcomes at Aravind Eye Hospitals, India

Abstract: Purpose To report trends in cataract surgery indications, visual acuity outcomes, complication rates and reoperation rates at ten Aravind Eye Hospitals in Tamil Nadu, India. Methods In this retrospective database study we analyzed seven years of data of cataract surgeries at Aravind during January 1, 2012 to December 31, 2018. Our main outcome measures were preoperative and 1-month postoperative uncorrected visual acuity (UCVA) and best-corrected visual acuity (BCVA); and rates of intraoperative complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…2 Beyond the low engagement with the issue of climate change by the international research community, the other finding of this Review is the difference between the carbon footprint of similar services delivered in different settings: one phacoemulsification in the UK produces more than 20 times the greenhouse gas emissions of one phacoemulsification in India, with both having excellent clinical outcomes. 22,26,63 This contrast is also portrayed visually in images taken for The Lancet Global Health Commission on Global Eye Health: vision beyond 2020, 20 which showed the waste generated for one phacoemulsification procedure in the UK and the waste produced for 32 phacoemulsifications in India (figure 3).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…2 Beyond the low engagement with the issue of climate change by the international research community, the other finding of this Review is the difference between the carbon footprint of similar services delivered in different settings: one phacoemulsification in the UK produces more than 20 times the greenhouse gas emissions of one phacoemulsification in India, with both having excellent clinical outcomes. 22,26,63 This contrast is also portrayed visually in images taken for The Lancet Global Health Commission on Global Eye Health: vision beyond 2020, 20 which showed the waste generated for one phacoemulsification procedure in the UK and the waste produced for 32 phacoemulsifications in India (figure 3).…”
Section: Discussionmentioning
confidence: 95%
“…Where comparable outcomes can be delivered at reduced environmental costs, 49,63 an opportunity exists for the migration of practice; convenient lifecycle assessment tools such as the Eyefficiency App permit the evaluation and cyclical audit of the carbon footprint of cataract surgical services. 31,38 However, authors also attribute the large difference between the Indian and UK cataract services to the policies in HIC settings that prevent the adoption of sustainable practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nderitu and Ursell have shown a significantly increased operative time when surgery is performed by a junior surgeon [ 15 ]. In the last decade, rates of intraoperative complications after cataract surgery decreased a lot due to improved instrumentation and techniques and training programs [ 18 , 19 ]. Ravindran et al found a rate of intraoperative complications for phacoemulsification that fell from 1.3% in 2012 to 0.7% in 2018 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, rates of intraoperative complications after cataract surgery decreased a lot due to improved instrumentation and techniques and training programs [ 18 , 19 ]. Ravindran et al found a rate of intraoperative complications for phacoemulsification that fell from 1.3% in 2012 to 0.7% in 2018 [ 18 ]. In 2018, Staropoli et al published a rate of intraoperative complications of 2.4% in the simulator-trained resident group versus 5.1% in the simulator-naïve group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%